La evaluación de proyectos de Gramática Básica según el modelo SAMR Evaluating Basic Grammar Projects, Using the SAMR Model - Giangiulio Lobo, Alejandra (2017)
The research evaluates the projects assigned in two basic grammar courses of the English teaching majors, at Universidad Nacional in Costa Rica, using the SAMR framework for evaluating learning activities that implemented Information and Communication Technologies. First, the relevance of the use of these projects is presented. Second, the SAMR framework is explained. Third, the six different projects are discussed and evaluated according to the SAMR framework, taking into consideration the students’ perceptions. Recommendations are given regarding the use of technology to learn grammatical structures.